The incorporation of heterovalent copper-oxo and copper-halide clusters for the fabrication of three porous cluster organic frameworks: syntheses, structures and iodine adsorption/release study. Issue 4 (7th January 2020) - Liu, Jin-Hua; Zhang, Jing; Zhao, Dan; Lin, Li-Dan; Sun, Yan-Qiong; Li, Xin-Xiong; Zheng, Shou-Tian
Abstract : Three porous cluster organic frameworks constructed from the paddle-wheel Cu2 (CO2 )4 and cubane-like Cu4 I4 clusters have been synthesized and characterized. Interestingly, compound 2 shows moderate gas uptake ability and I2 adsorption/release feature. Abstract : Three porous heterovalent cluster organic frameworks Cu2 (H2 O)(Cu4 I4 )(INA)4 ·solvent (1 ), Cu2 (H2 O)2 (Cu4 I4 )2 (INA)4 (DABCO)2 ·2DMA (2 ) and [(Cu2 )2 (PVBA)8 (Cu4 I4 )]·DMF (3 ) (HINA = isonicotinic acid, DABCO = 1, 4-diazabicyclo[2.2.2]octane, HPVBA = 4-(2-(4-pyridyl)ethenyl) benzoic acid, DMF = N, N ′-dimethylformamide, DMA = N, N ′-dimethylacetamide) have been solvothermally synthesized and structurally characterized. Crystal structure analyses indicate that compounds 1 and 2 are constructed from planar four-connected Cu2 (CO2 )4 secondary building units (SBUs) and tetrahedral four-connected Cu4 I4 SBUs, while compound 3 is composed of octahedral six-connected Cu2 (CO2 )4 SBUs and tetrahedral four-connected Cu4 I4 SBUs. All these frameworks possess nano-sized 1-dimensional channels. Furthermore, the thermal and chemical stabilities, gas adsorption properties and iodine adsorption/release ability of compound 2 have been systematically studied.